Effect of Green Tea Extract to the Degree of Knee Joint Damage and Nitric Oxide Levels in the Rabbit Osteoarthitis Model - Susmiarsih, Tri Panjiasih; Hadi, Restu Syamsul; Sofwan, Achmad; Kuslestari, K; Razari, Intan (Universitas Muhammadiyah Surakarta, 2019)
Osteoathritis (OA) is characterized by degeneration of articular cartilage, subchondral bone, synovial fluid and synovium. Nitric oxide (NO) is proinflammatory cytokine that play a significant role in the pathogenesis of OA via cartilage and bone degradation by synovial inflammation. Green tea is a novel functional food for treating osteoarthritis and inhibiting the production of inflammatory mediators such as nitric oxide. This study aimed to evaluate the effects of green tea extract to the nitric oxide levels and degree of knee joint damage in the rabbit osteoarthitis model. The Freud’s adjuvant complete was performed to induce OA, as many as sixteen male rabbits (New Zealand white) were randomly divided into four groups: adjuvant injection, adjuvant and green tea (injection), adjuvant and green tea (per oral), and control group. The control group only received drinking water, the Freud adjuvant (0.2 ml) and green tea extract (200 mg/kg bw) were orally and injection administered for eight weeks. The articular cartilage damage was evaluated histologically according to MANKIN score. NO levels were determined by nitric oxide assay. Data was analysed by Chi square test. The result of this study showed the surface structure damage of cartilage increased after adjuvant-induced. Green tea extract decrease significantly (p=0.02) the degree of knee joint damage after adjuvant-induced in rabbit osteoarthritis models. NO levels increased after OA induction. The green tea extract administration (via injection) can significantly (p = 0.038) decrease NO levels compare to adjuvant group. Green tea extract decrease the knee joint damage and NO proinflamantory levels in rabbit of osteoarthritis model